2002
DOI: 10.1016/s0735-1097(01)01775-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockers in heart failure: meta-analysis of randomized controlled trials

Abstract: This meta-analysis cannot confirm that ARBs are superior in reducing all-cause mortality or HF hospitalization in patients with symptomatic HF, particularly when compared with ACEIs. However, the use of ARBs as monotherapy in the absence of ACEIs or as combination therapy with ACEIs appears promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(54 citation statements)
references
References 29 publications
2
46
2
4
Order By: Relevance
“…Patients were in New York Heart Association functional classes II and III and had LVEF Ͻ0. 35. Both of these were digoxin discontinuation trials.…”
Section: Proved and Radiance Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were in New York Heart Association functional classes II and III and had LVEF Ͻ0. 35. Both of these were digoxin discontinuation trials.…”
Section: Proved and Radiance Trialsmentioning
confidence: 99%
“…35 A more recent trial 36 also showed that ARBs were not superior to ACE-I in the treatment of heart failure or LV dysfunction after myocardial infarction. In the Randomized ALdactone (spironolactone) Evaluation Study for congestive heart failure (RALES) trial, 37 patients in the spironolactone group received digoxin (75%), diuretics (100%), ACE-I/ARB (95%), and ␤-blockers (11%).…”
Section: Advantages Of Digitalis Therapy In Clinical Hfmentioning
confidence: 99%
“…While our results are restricted to patients with essential hypertension, the agents studied here have been compared in large studies and in systematic reviews for related conditions such as congestive heart failure, ischemic heart disease, and chronic kidney disease. 120,123,124 These systematic reviews, like ours, have limited inclusion to studies conducted in patients with the target condition; however, these reviews have examined an overlapping set of efficacy and safety outcomes. As a result,…”
Section: Study Namementioning
confidence: 99%
“…17 However, a 17% reduction in hospital admissions, relative to placebo, was observed with the use of ARBs. 17,18 The current review had 3 specific objectives: to elucidate the reasons for conflicting data on the outcome of cancer incidence between the 3 meta-analyses, to understand the impact of outcome reporting bias on meta-analysis of clinical trials, and to describe the role that health care regulators could play in minimizing the occurrence of reporting bias.…”
Section: Introductionmentioning
confidence: 99%